Relation of Blood Omentin-1 and Some Biochemical Parameters With Body Mass Index in Patients of Nonalcoholic Fatty Liver Disease - Hassan Ali, Haneen; Shaalan Sahab, Khalid (ASJ - Academic Science Journal, 2024)
Nonalcoholic fatty liver disease (NAFLD) is a condition of increasing fat in liver of individualswho do not consume significant amount of alcohol. The study aimed to estimate Omentin-1,insulin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkalinephosphatase (ALk) , albumin, globulin, total protein, CRP, Triglyceride (TG), total cholesterol(TC), high density lipoprotein (HDL), low density lipoprotein (LDL), very low densitylipoprotein (VLDL) in the serum of NAFLD patients, and find the relationship of variation inomentin-1 and Some Biochemical Parameters with body mass index(BMI) in Patients ofNAFLD And comparing them with to the healthy ones.Ninety people were involved in this study (60 were patients with NAFLD and 30 healthyindividuals) from Al-Muqdudia General Hospital in Diyala province, Iraq, during the period1/10/2021 to 30/12/2021. The ELISA Kit was used to detect serum omentin-1. A rapidquantitative assay HS-INSULIN-CHECK-1 is used to estimate the of insulin. The CRP-latex isa slide agglutination test for the quantitive and semi-quantitive detection of C-reacive protein(CRP) in human serum. in serum AST, ALT, ALP, Albumin Globulin, Total Protein, TG, TCand HDL tests were assessed using an Semi automated spectrophotometer (Humalyzer Primus).Serum omentin-1 levels were higher in patients than in healthy subjects with significantdifferences (p0.05). The omentin-1 showed not significant association withthe anthropometries measurements.